Design of submicron structures with superhydrophobic and oleophobic properties on zinc substrate. (15th November 2015) - Hao, Li; Yu, Sirong; Han, Xiangxiang; Zhang, Shanbao
Abstract: A superhydrophobic and oleophobic surface was demonstrated on Zn substrate via a composite method using chemical etching, hydrothermal reaction, and fluorinated modification. The surface morphology with aligned ZnO rods that grew almost perpendicularly on Zn substrate and had flat hexagonal crystallographic planes played a key role in the achievement of the superhydrophobicity and oleophobicity. The Zn surface with aligned ZnO rods was then made superhydrophobic and oleophobic with maximum distilled water and peanut oil contact angles (CAs) of 152° and 146°, respectively, by further fluorinated modification, and the sliding angle (SA) for distilled water was less than 10°. Moreover, on the basis of the classical models (Wenzel's and Cassie's model), an improved model was established to analyze the influence of the surface morphology on the wettability. The effect of the experimental parameters including the hydrothermal temperature and the concentration of the chemical etching agent on the surface morphology and the wettability were examined, and then the optimum parameters were obtained. This method is simple and inexpensive, and has potential application in depositing Zn coating that can provide both corrosion resistance and oleophobicity to the substrate metals. Graphical abstract: Highlights: A superhydrophobic and oleophobic surface was fabricated on zinc substrate. Zinc was both the substrate and the source of zinc ions in hydrothermal reaction. An improved model was to analyze the effect of the surface morphology on the wettability. The effect of experimental parameters on the surface morphology and the wettability were examined.